2017
DOI: 10.1002/hyp.11347
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater management network effectiveness and implications for urban watershed function: A critical review

Abstract: Deleterious effects of urban stormwater are widely recognized. In several countries, regulations have been put into place to improve the conditions of receiving water bodies, but planning and engineering of stormwater control is typically carried out at smaller scales. Quantifying cumulative effectiveness of many stormwater control measures on a watershed scale is critical to understanding how small‐scale practices translate to urban river health. We review 100 empirical and modelling studies of stormwater man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
128
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 152 publications
(225 reference statements)
1
128
2
1
Order By: Relevance
“…The speed of SCM installation in suburban and urban watersheds has outpaced our understanding of how effective watershed‐scale installation of SCMs is for mitigating streamflow response to precipitation events. There are few empirical, watershed‐scale studies of the hydrologic impacts of installing a network of SCMs, and modelling studies may overestimate the effect of SCM treatment on stormflow response (Jefferson et al, ; Li, Fletcher, Duncan, & Burns, ). Therefore, there is a critical need for empirical monitoring to assess and validate the hydrological performance of watershed‐scale SCM implementation, rather than a reliance on individual SCM performance and modelling studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The speed of SCM installation in suburban and urban watersheds has outpaced our understanding of how effective watershed‐scale installation of SCMs is for mitigating streamflow response to precipitation events. There are few empirical, watershed‐scale studies of the hydrologic impacts of installing a network of SCMs, and modelling studies may overestimate the effect of SCM treatment on stormflow response (Jefferson et al, ; Li, Fletcher, Duncan, & Burns, ). Therefore, there is a critical need for empirical monitoring to assess and validate the hydrological performance of watershed‐scale SCM implementation, rather than a reliance on individual SCM performance and modelling studies.…”
Section: Introductionmentioning
confidence: 99%
“…The speed of SCM installation in suburban and urban watersheds has outpaced our understanding of how effective watershed-scale installation of SCMs is for mitigating streamflow response to precipitation events. There are few empirical, watershed-scale studies of the hydrologic impacts of installing a network of SCMs, and modelling studies may overestimate the effect of SCM treatment on stormflow response (Jefferson et al, 2017;Li, Fletcher, Duncan, & Burns, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is a substantial reduction and again emphasizes the potential for SCMs to offset increased NO 3 loads from increases of impervious surface during urban development. This effect of SCMs on NO 3 loads has been shown in empirical studies (Hale et al, ; Pennino et al, ), but the number of watershed scale studies like this are limited (Jefferson et al, ). The effects of SCM connectivity on N loads are also amplified in warmer months relatively to cooler ones (Figures b and c).…”
Section: Discussionmentioning
confidence: 73%
“…Modeling studies have shown that EI predicts runoff volumes and storm event peak discharges well (Dewals et al, ; Guo, ; Lee & Heaney, ; Palla & Gnecco, ; Schoener, ; Shields & Tague, ). However, there is currently a lack of empirical studies examining the watershed‐scale effects of connectivity to SCMs on water quality, and only a few modeling studies exist (Jefferson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This can be done by characterizing SCMs as well as understanding their cumulated affect in a larger system, which is reported to be challenging and empirically less attended [17].…”
Section: Introductionmentioning
confidence: 99%